Pengaruh Pengalaman Kerja, Otonomi Kerja, Dan Tekanan Peran Terhadap Kinerja Auditor Pada Kantor Akuntan Publik Di Bandar Lampung (Study Kasus pada Kantor Akuntan Publik di Bandar Lampung) - Yunus Fiscal; . Syilvya; Muh. Nur Ram'dhan (Universitas Bandar Lampung (UBL), 2012)
Public Accounting Firm (KAP) is a form of organization that has licensed public accountant in accordance with legislation that seeks the provision of professional services in the field of public accounting practice. CPAs function as an external audit will be effective and optimal performance if supported by auditors. To improve the performance of an auditor, not only requires only intellectual, but also needed a good work experience, freedom and independence in carrying out the duties and powers of office for each professional. Method of data collection is by using questionnaires distributed to the auditor in public accounting firm in Bandar Lampung, while the analytical tools used are qualitative analysis and quantitative analysis. The results showed that work experience and job autonomy positive and significant impact on the performance of auditors, while the role of pressure and a significant negative effect on the performance of auditors. Based on the above conclusion, it is suggested that public accounting firm auditors to limit the amount of workload and provide clear information to avoid conflicts and role.